Modal Sosial Pemimpin Nasional Pasca Pemilu 2004 - Idrus, Muhammad (Unisia, 2016)
The article below investigates the urgent need of a social capital fornational leader, especially in the context of Indonesian leader who chosen after public election 2004 in Indonesia. Social capital interm of psychology constitutes a traits that embedded at individu that forming the values of life, and those of regulations to facilitate a good cooperation. Talking the problem of Indonesian leadership nowadays, the expectation that emeges that leader who chosen by public election April, 5, 2004 is a leader really who characterized by Putnam, honesty and egalitarian who treate himself/ herself as a part of society. Hence, the important of the people of Indonesia direct, correct, control their leader so that they return to right way.